Use of electro-fenton process as treatment for nickel-containing wastewater from semiconductor industry - Encarnacion, Joanne O. (2008)
The study investigated the feasibility of applying Electro-Fenton process coupled with neutralization and settling in the treatment of nickel-containing wastewater similar to the effluent discharge from semiconductor industry. The effect of varying initial H2O2 and Fe2+ dosages, anode and electric current on the efficiency of Electro-Fenton was assessed. The degradation behavior of nickel with citric acid as its chelating agent was also compared with the degradation behavior of an industrial wastewater from an electroplating facility. Results show that degradation of citric acid wa imperative for the treatment of nickel. Furthermore, neutralization and settling played a great part in the removal of nickel in the wastewater. The optimum condition for the 85.19 nM nickel and citric acid solution was an Electro-Fenton process with an initial dosage of 2.10 M H2O2 and 127.78 mM Fe2+ at 1A and initial pH of 2. The nickel removal after the Electro-Fenton process 25.03%. Subjecting it further with neutralization, the nickel removal became 45.55% and finally a fter settling, a 95.37 nickel removal was achieved. The COD removal for the same condition was 71.88% after Electro-Fenton process, 82.81% after neutralization and 96.88% after settling. However, due to the marginal difference, Conventional Fenton process coupled with neutralization and settling can be used to minimize on the power cost and still be able to treat the synthetic wastewater containing nickel and citric acid. The synthetic wastewater behaves differently as compared to the industrial wastewater with respect to the H2O2 dosage. This would be due to the complexity of the industrial wastewater. The industrial water from the electroplating facility however needs the Electro-Fenton process coupled with neutralization and settling to treat the wastewater. This is important for COD removal. The highest COD removal of 88.10% wad 7.56 M H202 dosage, and initial FE2+ dosage of 127.78 mM, initial pH of 2, constant electric current of 1A, and reaction time of 8.75 hour. As for the nickel removal, the same H202 dosage gacwe the highest nickel removal of 90.93. Thus, the use of Advanced Oxidation Process before neutralization and settling was imperative since it helps in the nickel and COD removal. Simple coagulation and neutralization is insufficient in treating nickel containing wastewater.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Electrolytic oxidation; Sewage -- Purification -- Oxidation; Nickel wastes